Integrated Management of Knee Osteoarthritis Associated Hypertension with Naturopathy and Yoga: A Case Report - Singh, Poonam (International Research Journal of Ayurveda & Yoga, 2022)
Osteoarthritis of the Knees (OA Knees) also known as degenerative arthritis or degenerative joint disease is a group of mechanical abnormalities involving the degradation of joints, including articular cartilage and subchondral bone. Associated comorbid conditions such as hypertension increase the symptoms. Allopathic drugs taken to relieve the symptoms have their own side effects. The aim of treatment with naturopathy, yoga, and diet therapy is the reduction of symptoms and an increase in functional activities of patients with osteoarthritis of the knees. Naturopathy and therapeutic yogic exercises reduce pain, improve the strength of the joints, and support muscles and ligaments which provides good flexibility of the joints, and increases the range of motion. Diet plays a major role to prevent and control degeneration. A Vitamin D-rich diet helps to regenerate the joint wear and prevents worsening of the knee symptoms. Osteoarthritis may lead to early disability condition which needs to be managed as soon as possible. Osteoarthritic management requires a holistic approach.